The Effect of Social Cognitive Theory-Based Psychoeducation Towards Depression and Blood Pressure of Ischemic Stroke Patients - Tata Mahyuvi; Nursalam Nursalam (Journal for Quality in Public Health, 2020)
Introduction. Stroke places on the third rank in the world as the cause of death. Depression is a common psychology condition found in ischemic stroke patient and generally experienced hypertension. The aim of this research is to analyze the effect of social cognitive theory-based psychoeducation towards depression and blood pressure of ischemic stroke patient. Design. The design of this research is quasi-experiment by pre and post control group within. The population is 100 ischemic stroke patients in mental hospital Jemursari Surabaya, while the samples are 32 respondents. The sampling technique used is simple random sampling. The intervention group was given social cognitive theory-based psychoeducation for 15-30 minutes in 4 times session and the control group was given intervention as hospital standards. The data were analyzed by paired t-test with significant value α=0,05. Result. The result of the research revealed that there was a significant effect between depression and blood pressure before and after the treatment of social cognitive theory-based psychoeducation. It shown that depression intervention group p value=0,000 and systole and diastole p value=0,000. Discussion. Social cognitive theory-based psychoeducation was effective to decrease depression and blood pressure of ischemic stroke patient and it is highly recommended for the patient in the rehabilitation phase.